TAFSIR DAN CYBERFEMINISM DI MEDIA SOSIAL - Fuad Fansuri; Muhammad Fakih; Afita Nur Hayati; Misbahul Ramadhani; Rabi'atul Husni (JURNAL DARUSSALAM: Pemikiran Hukum Tata Negara dan Perbandingan Mazhab, 2025)
This article attempts to examine how feminist issues are disseminated through interpretation practices on virtual social media, a domain that has long been monopolized by men. Men are considered the primary actors in efforts to interpret holy verses. Consequently, there is a proliferation of gender-biased religious narratives promoted on social media. These narratives are predominantly dominated by a textual paradigm without regard for the context of the referenced verses, resulting in a biased delivery of the verses' core messages. This study employs a discourse analysis approach utilizing documentation techniques and library research. The primary data used as a reference in this study consists of posts from the Mubadalah.id account categorized as cyberfeminism tafsir (cyberfeminist exegesis) spanning the last year since the commencement of this research. The categorization of cyberfeminism tafsir on the Mubadalah.id account is based on the inclusion of Qur'anic verse translations and exegetical literature within its posts. The results of this study indicate that the cyberfeminism tafsir on the Mubadalah.id Instagram account illustrates concepts regarding the relationship between technology and women's empowerment through interpretative activities on social media. The characteristics of cyberfeminism tafsir applied by Mubadalah.id on their Instagram account are grounded in three fundamental principles: first, the interpretation of the Qur'an must provide benefits to all parties; second, the interpretation of the Qur'an must not reinforce the objectification of a specific gender; and third, the interpretation of the Qur'an encourages an equitable division of roles between genders.